Analisis Proses Pemutahiran Daftar Pemilih Dalam Daftar Pemilih Tetap (DPT) Pada Pemilu Tahun 2019 Di Kabupaten Gorontalo - Sarfan Tabo; Andi Agustang; Andi Muhammad Idkhan; Muten Nuna; Ramli Mobonggi (Jurnal Sosio Sains, 2021)
The purpose of this research is to describe and analyze the process of updating voter list in the final voter list (DPT) in General Election 2019 in KPU Gorontalo Regency. This research is motivated by the findings of Election Supervisory Body (BAWASLU) regarding the existence of 1,013,366 double DPTs in 76 districts and cities. Another claim is also made by a special team formed by Prabowo-Sandiaga Uno regarding the findings of 8,145,713 double DPTs (kompas.com, September 12th, 2018). The Permanent Voters List (DPT) becomes the basis for citizens’ political participation in general election (Pemilu). Community political participation has a very important role for the development of democratic politics in every country. In the context of elections, voters change from citizen participations to supports for illegitimate power through election competition among election participants. As a result of the problem of DPT, at the time of recapitulation of the revised DPT (DPTHP), the problem of double DPT cannot be separated from the absence of a policy for protecting personal data. The contents of DPT related to the personal identity of population have not become an absolute priority for the state to provide protection. It is also the duty of each stakeholder for their protection policy, in addition accessing for the public to the voter list up to the polling station (TPS) level. The result of the study shows that the stages of updating voter data that occurred in Election 2019 are indeed a long stage. This happens with the recommendation from BAWASLU and the input and response to the Election Permanent Voters List 2019 from the stages so that an extension is carried out by Indonesian KPU in order to create accurate and accountable voter data. This research uses qualitative research method namely descriptive research which tends to use analysis. Process and meaning (subject perspective) are more prominent in qualitative research. To improve the quality of the voter list, it is necessary to have a more adequate system and competent human resources in processing the permanent voter list.